Rheological characterization of a physically-modified waxy potato starch: Investigation of its shear-thickening mechanism. (November 2021) - Ang, Cai Ling; Tha Goh, Kelvin Kim; Lim, Kaiyang; Matia-Merino, Lara
Abstract: This study focuses on the rheological characterization of the time- and shear-dependence of a physically modified waxy potato starch through treatment at 120 °C for 30 min under continuous stirring. The starch sample exhibited time-dependency, where the viscosity increased with time at constant shear rates between 5 and 60 s −1 . Shear-induced gelation was also observed when the sample was sheared above 100 s −1 . The gel structure remained relatively stable within the experimental timeframe of 72 h at 20 °C. A minimum starch concentration of 1% w/w was required for shear-thickening and anti-thixotropy to be observed. This study showed that the formation of a shear-induced weak gel structure was not caused solely by hydrogen bonding, electrostatic, hydrophobic interactions or a combination of these forces. The formation of a weak gel structure was probably initiated first by shear which orientated the amylopectin molecules in the direction of shear. The 'stretched' amylopectin molecules subsequently facilitated closer proximity between polymer chains which promoted intermolecular association between polymer chains to take place. Graphical abstract: Image 1 Highlights: Waxy potato starch was treated at 120 °C for 30 min under shear. Shear-thickening behavior was detected above 1% w/w. The treated starch exhibited time-dependency rheological properties ≥5 s −1 . A shear-induced weak gel was observed upon shearing at ≥ 100 s −1 for 5 min. Thickening was not solely contributed by hydrogen bonding, electrostatic or hydrophobic interactions.